2021
DOI: 10.1186/s13053-021-00168-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel frequent BRCA1 recurrent variant c.5117G > A (p.Gly1206Glu) identified after 20 years of BRCA1/2 research in the Baltic region: cohort study and literature review

Abstract: Background Several recent studies in the Baltic region have found extended spectrum of pathogenic variants (PV) of the BRCA1/2 genes. The aim of current study is to analyze the spectrum of the BRCA1/2 PV in population of Latvia and to compare common PV between populations of the Baltic region. Methods We present a cohort of 9543 unrelated individuals including ones with cancer and unaffected individuals from population of Latvia, who were tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Remarkably, the c.1961delA variant demonstrates a noteworthy co-occurrence with the c.1016delA and c.3329delA variants, suggesting potential interactions or relationships among BRCA1 PVs that could influence disease development or other genetic outcomes. The observed significant association between specific somatic BRCA1 PVs namely, c.1961dupA and c.3329dupA in CRC patients in our results align with previous studies that have documented significant associations among these BRCA1 PVs not only in breast cancer cases [ 46 , 48 ] but also in ovarian cancer contexts [ 49 , 50 ] . This suggests a potential implication of these co-occurring PVs across different malignancies, pointing towards potentially underlying mechanisms or vulnerabilities linked to these genetic alterations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Remarkably, the c.1961delA variant demonstrates a noteworthy co-occurrence with the c.1016delA and c.3329delA variants, suggesting potential interactions or relationships among BRCA1 PVs that could influence disease development or other genetic outcomes. The observed significant association between specific somatic BRCA1 PVs namely, c.1961dupA and c.3329dupA in CRC patients in our results align with previous studies that have documented significant associations among these BRCA1 PVs not only in breast cancer cases [ 46 , 48 ] but also in ovarian cancer contexts [ 49 , 50 ] . This suggests a potential implication of these co-occurring PVs across different malignancies, pointing towards potentially underlying mechanisms or vulnerabilities linked to these genetic alterations.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the c.1961delA mutation is associated with a 2.8-fold rise in CRC risk when compared to controls. Notably, this mutation's implications extend to breast, ovarian, and hereditary cancer syndromes, as observed in South Korea [ 45 ], Baltic [ 46 ] and Brazil populations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another common mutation BRCA1 c.3756_3759delGTCT has been detected in some populations, such as Thai [55], Polish [56], Belarusian [57], Italian [58], French-Canadian [59], and Czech populations [60]. BRCA1 c.4065_4068del has been detected in some populations [61][62][63]. Another study showed that c.4065_4068del is one of the three most common BRCA1 variants in Chinese ovarian cancer patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…This variant was also detected by Yang et al among Malaysian BC patients in two different cases: the first one had a family history and was diagnosed at a very early age (23 years), and the other one had no family history and was diagnosed at 42 years old [42]. Furthermore, we also identified the c.1961delA (p.Lys654fs) BRCA1 pathogenic variant in seven patients, and it was previously reported as a recurrent founder mutation in BC patients in different countries and worldwide [43][44][45][46]. On the other hand, we identified eight different deleterious mutations in the BRCA2 gene.…”
Section: Discussionmentioning
confidence: 58%